Differential sialotranscriptomes of unfed and fed Rhipicephalus haemaphysaloides, with particular regard to differentially expressed genes of cysteine proteases - Yu, Xinmao (Parasit Vectors, 2015)
BACKGROUND: Rhipicephalus haemaphysaloides, a hard tick, is a common ectoparasite and can be found in many countries. It is recognized as the primary vector of bovine babesiosis in the south of China. During blood feeding, the tick’s salivary glands secret numerous essential multifunctional proteins. In this study, a R. haemaphysaloides salivary gland transcriptome was described following the production and analysis of the transcripts from the two cDNA libraries of unfed and fed female ticks. The study focused on the differentially expressed genes and cysteine proteases, which play essential roles in the tick life cycle, that were detected most commonly in the up-regulation libraries. METHODS: The sialotranscriptome was assembled and analyzed though bioinformatic tools and the cysteine protease which is differentially expressed form sialotranscriptome were confirmed by Real-time PCR in salivary glands and different developments of ticks. RESULTS: On the basis of sequence similarities with other species in various databases, we analyzed the unfed and fed sialotranscriptome of R. haemaphysaloides to identify the differentially expressed proteins secreted from the salivary glands during blood feeding and to investigate their biological functions. There were 25,113 transcripts (35 % of the total assembled transcripts) that showed significant similarity to known proteins with high BLAST from other species annotated. In total, 88 % and 89 % of the sequencing reads could be mapped back to assembled sequences in the unfed and fed library, respectively. Comparison of the abundance of transcripts from similar contigs of the two salivary gland cDNA libraries allowed the identification of differentially expressed genes. In total, there were 1179 up-regulated genes and 574 down-regulated genes found by comparing the two libraries. Twenty-five predicted cysteine proteases were screened from the transcript databases, whereas only six protein molecules were confirmed by gene cloning and molecular expression in E.coli which all belonged to the cysteine protease family. Bioinformatic evolutionary analysis showed the relationship of cysteine proteases in ticks with those of other species, suggesting the origin and conservation of these genes. Analysis of sequences from different tick species indicated the further relationships among the proteases, suggesting the closely related function of these genes. Thus, we confirmed their changes in unfed, fed and engorged ticks and salivary glands. The dynamic changes revealed their important roles in the tick life cycle. CONCLUSIONS: Our survey provided an insight into the R. haemaphysaloides sialotranscriptome. The dynamic changes of cysteine proteases in ticks will assist further study of these proteases, which may contribute to the development of anti-tick vaccines or drugs, as well as improving understanding of the roles of cysteine proteases in the tick life cycle. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-015-1213-7) contains supplementary material, which is available to authorized users.